What Drives Islamic Banking Stability in ASEAN? The Mediating Role of Good Governance - Zainal Abidin; Ulfi Kartika Oktaviana; Habil Khairat (Shirkah: Journal of Economics and Business, 2026)
This study examines the determinants of Islamic banking stability in the ASEAN region by investigating the mediating role of good governance in the relationship between internal and external risk factors and bank stability. While prior studies have primarily focused on the direct determinants of banking resilience, limited attention has been paid to the intermediary role of governance in shaping Islamic banking stability. This study addresses this gap by integrating good governance into a comprehensive analytical framework. Using secondary panel data from Islamic banks in Indonesia and Malaysia during the 2019–2023 period, the study employs multiple regression analysis and the Sobel test to assess mediation effects. Data were collected from individual bank financial reports, central bank databases, and the Worldwide Governance Indicators (WGI). The findings reveal that credit risk negatively and significantly affects Islamic banking stability, whereas capital risk and exchange rates exert positive and significant effects. Interest rates demonstrate a positive but insignificant influence. Good governance significantly enhances Islamic banking stability and mediates the effects of capital risk and exchange rates, but not those of credit risk and interest rates. These findings underscore the strategic importance of governance mechanisms in strengthening the resilience and sustainability of Islamic banking institutions amid regional and global financial uncertainty.